Word Use as an Unobtrusive Predictor of Early Departure From Organizations. (March 2021) - Baek, Young Min; Ihm, Jennifer
Past studies have emphasized members' personality as an important predictor of departure from organizations, but the measurement of this factor has mostly relied on self-judged personality. As alternatives to self-judged personality, our study examines how two unobtrusive measures—others-judged personality and computerized text analytic results through Linguistic Inquiry and Word Count 2015 (Pennebaker et al., 2015)—are related to members' departure from organizations ( N = 49). Drawing from internal personnel evaluations (i.e., others-judged personality), text (i.e., self-introduction documents that applicants submitted when applying to the organization), and behavioral data (i.e., actual stay in the organization), this study indicates that unobtrusive measures significantly predict members' length of stay and that simultaneous use of both measures better predicts members' length of stay in the organization than either one separately. However, text analytic results through Linguistic Inquiry and Word Count 2015 predict members' departure more robustly. This study expands the theoretical meaning of personality and provides practical ways to predict people's organizational behaviors.